Sistem Manajemen Anti-Penyuapan ISO 37001:2016 dan Pencegahan Praktik Korupsi di Sektor Pelayanan Publik - Holman Fasa, Angga Wijaya; Sani, Sofia Yuniar (Komisi Pemberantasan Korupsi, 2020)
Bribery frequently occurs in public service sector. As one of the latest instruments, the Anti-Bribery Management System ISO 37001: 2016 is carried out to prevent this act. This study highlights the urgency and the efforts to implement this system. To attain these purposes, a qualitative method with a descriptive analysis approach was employed. The result show that: first, ISO 37001: 2016 has yet to be significantly implemented because there is no empirical evidence concerning the improvements in the quality of the bribery prevention. Second, the system is applied by creating a public service management system based on the change of leadership pattern, the change of governance, and the reinforcement of public monitoring.